About the dual soft sets theory. (17th November 2022) - Al-Swidi, Luay A.; Hadi, Mustafa Hasan; Ali, Reyadh D.
Abstract: Soft sets play a prominent role in solving many engineering and scientific problems. After a thorough study of it and to the fuzzy sets, there were real scientific and engineering problems that these sets could not give a typical solution to them, so the idea of expanding these sets came up and we call them the dual soft sets. Also we defined the dual soft points differently to those sets.